Association Between the Severity of Nephrolithiasis and the Degree of Hepatic Steatosis on Non-Contrast Abdominal CT Scan - Fransiskus Aryo Pratomo; Adi Soekardi; Desi Novianti (Universitas Pahlawan Tuanku Tambusai, 2026)
Introduction: Nephrolithiasis and hepatic steatosis are two conditions that frequently co-occur and are hypothesized to share common pathophysiological pathways through metabolic syndrome. However, studies quantitatively exploring the relationship between the degree of hepatic steatosis and kidney stone volume (total stone volume/TSV) remain limited. Methods: This study employed an analytical cross-sectional design using retrospective data from electronic medical records and the PACS system at RSU Royal Prima Medan from March to December 2025 with a total of 84 subjects. The degree of hepatic steatosis was assessed based on liver attenuation values on non-contrast CT-scan. Total stone volume was calculated based on stone dimension measurements using 3D Slicer application. Bivariate analysis followed by multivariate analysis using linear regression to control for confounders. Results: The mean age of subjects was 51.38 ± 11.13 years, with a male proportion of 54.8%. The prevalence of visceral obesity (VFA >100 cm²) was 70.2%. Most subjects (84.5%) had hepatic steatosis. The Spearman correlation test showed a significant positive correlation between the degree of hepatic steatosis and TSV (ρ = 0.48; p < 0.001). Linear regression analysis confirmed that hepatic steatosis was an independent predictor of TSV after controlling for age, sex, and visceral obesity (β = 0.403; p < 0.001), with a model R² value of 0.266. Conclusion: There is a significant and independent association between the degree of hepatic steatosis and total stone volume in patients with nephrolithiasis. Screening for hepatic steatosis in nephrolithiasis patients should be considered as part of a holistic management approach. Keywords: Nephrolithiasis, hepatic steatosis, total stone volume, metabolic syndrome, visceral obesity